Correlating Events with Time Series for Incident Diagnosis - Luo, Chen; Lou, Jian-Guang; 林庆维, Qingwei Lin; Fu, Qiang; Ding, Justin; Zhang, Dongmei; Wang, Zhe (SigKDD'14, 2014)
As online services have more and more popular, incident diagnosis has emerged as a critical task in minimizing the service downtime and ensuring high quality of the services provided. For most online services, incident diagnosis is mainly conducted by analyzing a large amount of telemetry data collected from the services at runtime. Time series data and event sequence data are two major types of telemetry data. Techniques of correlation analysis are important tools that are widely used by engineers for data-driven incident diagnosis. Despite their importance, there has been little previous work addressing the correlation between two types of heterogeneous data for incident diagnosis: continuous time series data and temporal event data. In this paper, we propose an approach to evaluate the correlation between time series data and event data. Our approach is capable of discovering three important aspects of event-timeseries correlation in the context of incident diagnosis: existence of correlation, temporal order, and monotonic eﬀect. Our experimental results on simulation data sets and two real data sets demonstrate the eﬀectiveness of the algorithm.